2002
DOI: 10.1074/jbc.m205590200
|View full text |Cite
|
Sign up to set email alerts
|

Monensin Mediates a Rapid and Selective Transport of Pb2+

Abstract: The carboxylic acid ionophore monensin, known as an electroneutral Na ؉ ionophore, an anticoccidial agent, and a growth-promoting feed additive in agriculture, is shown to be highly efficient as an ionophore for Pb 2؉ and to be highly selective for Pb 2؉ compared with other divalent cations. Monensin transports Pb 2؉ by an electroneutral mechanism in which the complex PbMonOH is the transporting species. Electrogenic transport via the species PbMon ؉ may also be possible. Monensin catalyzed Pb 2؉ transport is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 56 publications
(45 reference statements)
3
20
1
Order By: Relevance
“…Consistent with its mode of action, the effectiveness of Monensin appears to be sensitive to the local cation environment [22][23][24][25][26]. Very recently it was shown that polyether antibiotics are highly effective as ionophores for Pb 2+ and could react with a broad range of cations not just monovalent ones as often assumed [27][28][29][30].…”
Section: Introductionmentioning
confidence: 91%
“…Consistent with its mode of action, the effectiveness of Monensin appears to be sensitive to the local cation environment [22][23][24][25][26]. Very recently it was shown that polyether antibiotics are highly effective as ionophores for Pb 2+ and could react with a broad range of cations not just monovalent ones as often assumed [27][28][29][30].…”
Section: Introductionmentioning
confidence: 91%
“…Although there is some evidence that monensin reacts with divalent metal ions, only a limited number of research teams are studying the antibiotic reactions with metal ions other than monovalent representatives [33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…2 compares the transport activity of P3CA-15C5 to that of monensin [13] and ionomycin [12]. The concentrations of the ionophores were chosen to ensure that the rates of cation transport occurred on a reasonable time scale (e.g., 5-15 min.).…”
Section: Resultsmentioning
confidence: 99%
“…1), transport Pb 2+ across biological membranes with high selectivity over other divalent cations [12][13][14], and that they can enhance the elimination of Pb 2+ from cultured cells [12] and rats [13]. Although these naturally occurring compounds have favorable transport properties, their structures are difficult to modify in a systematic fashion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation